GEOGRAPHICAL INFORMATION SYSTEM ANALYSIS PBB BLOCK MAP (CASE STUDY DESA GAJAHAN KABUPATEN KARANGAYAR - Yanto, Fendi Hary; Suryoto, Suryoto; Kurnianingsih, Oktavia (ASTONJADRO, 2021)
Geographic Information Systems (GIS) have become very interesting and provide hope and the development of information and communication technology. One of the efforts to support the management of PBB geospatial data is by developing a Spatial Data Infrastructure (IDS). To determine the quality of geospatial data used in PBB management and the condition and readiness of IDS for PBB. A GIS-based computer program was used it. This study aims to determine the quality of geospatial data used to manage PBB in Gajahan Village, Colomadu District, Karngayar Regency. We collected data using observation and documentation techniques and data analysis of the PBB Block Map using the Arcgis software. The results showed that the position was less accurate in terms of geospatial data quality and the geometric shape had similarities. Also, the digitized results of the PBB block map can be used to support policymaking in local governments. However, the results of interviews with village officials were that they could only read old maps and could not update new data.